Pengaruh Pendapatan Domestik Regional Bruto (PDRB) terhadap Kemiskinan di Kabupaten/Kota Provinsi Sumatera Selatan - Rahmawati Apia; Liliana Liliana; Sri Rahayu Wulaningsih; Deta Septea (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2026)
Poverty remains a central issue in regional development, particularly in areas with pronounced economic disparities such as South Sumatra Province. This study aims to examine the effect of Gross Regional Domestic Product (GRDP) on the poverty rate across regencies and cities in South Sumatra during the period 2020–2024. A quantitative research approach was employed using panel data regression analysis, supported by descriptive statistics and classical assumption tests. The empirical findings indicate that GRDP has a negative and statistically significant effect on poverty, suggesting that an increase in regional economic capacity contributes to reducing poverty levels. However, the relatively small coefficient signifies that economic growth has not been fully inclusive and is influenced by the structural characteristics of each region. The Fixed Effect Model was identified as the most appropriate specification, highlighting the existence of heterogeneity across districts that shapes the relationship between GRDP and poverty. These results underscore the need for development strategies that not only promote economic growth but also ensure an equitable distribution of its benefits through the reinforcement of labor-intensive sectors, enhancement of human capital, and strengthening of local economic structures. The study provides valuable insights for regional policymakers in designing more effective and sustainable poverty alleviation strategies.